Social Cognition in Down Syndrome: Face Tuning in Face-Like Non-Face Images - Pavlova, Marina A.; Galli, Jessica; Pagani, Federica; Micheletti, Serena; Guerreschi, Michele; Sokolov, Alexander N.; Fallgatter, Andreas J.; Fazzi, Elisa M. (Frontiers in Psychology, 2018)
Individuals with Down syndrome (DS) are widely believed to possess considerable socialization strengths. However, the findings on social cognition capabilities are controversial. In the present study, we investigated whether individuals with DS exhibit shortage in face tuning, one of the indispensable components of social cognition. For this purpose, we implemented a recently developed Face-n-Food paradigm with food-plate images composed of food ingredients such as fruits and vegetables. The key benefit of such ‘face like non-face’ images is that single elements do not facilitate face processing. In a spontaneous recognition task, 25 children with DS aged 9 to 18 years were presented with a set of Face-n-Food images bordering on the Giuseppe Arcimboldo style. The set of images was administered in a predetermined order from the least to most resembling a face. In DS individuals, thresholds for recognition of the Face-n-Food images as a face were drastically higher as compared not only with typically developing controls, but also with individuals with autistic spectrum disorders and Williams-Beuren syndrome. This outcome represents a significant step towards better conceptualization of visual social world in DS and neurodevelopmental disorders in general.